VALUASI EKONOMI DAN PENGEMBANGAN POTENSI PARIWISATA DANAU LABUAN CERMIN DI KECAMATAN BIDUK-BIDUK KABUPATEN BERAU PROVINSI KALIMANTAN TIMUR - Jevon Ona Ivena; Idiannor Mahyudin; Emmy Sri Mahreda; Wahyuni Ilham (Universitas Lambung Mangkurat, 2016)
Natural attractions Labuan Cermin Lakes one of the potential of this attraction to be developed in order to increase investment, employment, business opportunity and ultimately to improve the welfare of society. The development of tourism sector in the economy has a trickle-down effect to other sectors. This study aims to identify the conditions of the environmental setting Subdistrict Biduk-biduk in terms of the socio-economic and cultural as well as the structure of the population, analyzing the perception of tourists to the natural attractions of Labuan Cermin Lakes, analyzing the growth of travelers who make Danau Labuan Cermin as a tourist destination, analyze the economic valuation of resource benefits environment and natural nature Labuan Cermin Lakes and designing models of development and management of Labuan Cermin Lakes nature in a sustainable manner. The method used is descriptive analysis method, analysis Travel Cost Method and SWOT analysis by respondents as many as 100 tourists and is supported by other primary and secondary data. The results based on primary and secondary data, Subdistrict Biduk-biduk with an area of 3.002.99 km, tropical climate and altitude of 1 (one) to 3 (three) meters above sea level. The total population of 5,631 inhabitants with a growth of 3.38% in 2014. The majority of fishermen and coconut plantations for copra. There are three tourist destinations, Labuan Cermin Lakes, Kaniungan Island and Bidadari Waterfalls. Perception rating of the facility Labuan Cermin Lakes is quite satisfactory with the percentage of 30% and the perception of tourists to services is 51%. Trend tourists who come to the tourist attraction of Labuan Cermin Lakes continue to increase from year to year with forecasts in 2016 to 2021 there was an increase of 12.4% annually. The magnitude of the economic value of natural resources and environmental benefits nature Labuan Cermin Lakes, 100 respondents from eight zones pay to enjoy the natural scenery of Lake Labuan Cermin Rp.1.099.437,- and if in 2015 as many as 22 504 tourists then obtained the value of tourism resources of Labuan Cermin Lakes Rp. 24,741,741,500,- as well as the surplus value amounted Rp.2.969.008.980,- travel traveler growth at 12.4% per year. Shape the direction of the development strategy of Labuan Cermin Lakes nature in a sustainable manner, Labuan Cermin Lakes facilities must have a good support for, the development of additional recreational facilities, development of creative entrepreneurial community and increased accessibility to Labuan Cermin Lakes.